Global value chains and income inequality in Africa - Yazeed Abdul Mumin; Williams Ali (Research Network Sustainable Global Supply Chains, 2025)
Recent technological advances and policy initiatives present Africa with enormous growth potential from participating in global value chains (GVCs). However, the widening income inequality is raising questions as to whether participation in GVCs plays any role in this observed phenomenon. Despite the increased attention on regional and global value chains, and on income inequality in Africa, little attention has been given to investigating the potential nexus between both. This study investigates the impacts of GVC participation on income inequality and the underlying mechanisms in Africa. We applied the instrumental variable (IV) approach to address potential endogeneity between GVC participation and income inequality. We find that participation in GVCs substantially reduces income inequality in Africa, which is largely through increased relative prices of exports, access to improved technologies and economic upgrading.
Keywords: 330